Regional and local development in times of polarisation. Re-thinking spatial policies in Europe. - (:unkn) unknown (Palgrave Macmillan, 2019)
Despite the emphasis of the European Regional Policy on territorial cohesion, regional disparities have been increasing within Europe in the past years. The metropolitan areas in almost all countries are considerably growing while regions outside of agglomerations are stagnating or even declining. Against this background this book aims to provide an understanding of the underlying processes of polarisation and related regional and local policies.This open access volume contributes to the debates about polarisation and regional development by focussing on questions of spatial justice, power distribution and policy transfer. Theoretical and empirically grounded contributions show that European policies are indeed reproducing socio-spatial inequalities instead of challenging them. The book shows further the existing potentials and limits of individuals, economic, political and civil society actors to respond to polarisation on the regional and local level.In this book conceptual thoughts on polarisation, regional policy and regional development are combined with empirical research and resulting implications for policymaking. As such, it is a valuable source for early career students and researchers as well as professionals in the field of regional and economic development, policy consultants, and policy makers.
Keywords: Regionalpolitik; Regionalplanung; Regionalentwicklung; Stadtentwicklung; Siedlungsstruktur; Raumstruktur; Kohäsion; Polarisierung; Regionale Disparität; Reproduktion; Wachstum; Schrumpfung; Peripherie